Prescription Pattern of Chinese Herbal Products for Diabetes Mellitus in Taiwan: A Population-Based Study. (17th June 2013) - Huang, Chung-Yu; Tsai, Yueh-Ting; Lai, Jung-Nien; Hsu, Feng-Lin
Abstract : Background. Traditional Chinese medicine (TCM), when given as a therapy for symptom relief, has gained widespread popularity among diabetic patients. The aim of this study is to analyze the utilization of TCM among type 2 diabetic patients in Taiwan. Methods. The use of TCM for type 2 diabetic patients were evaluated using a randomly sampled cohort of 1, 000, 000 beneficiaries recruited from the National Health Insurance Research Database. Results. Overall, 77.9% ( n = 31, 289 ) of type 2 diabetic patients utilized TCM and 13.9% ( n = 4, 351 ) of them used TCM for the treatment of type 2 diabetes. Among the top ten most frequently prescribed herbal formulae, four remedies, Zhi-Bo-Di-Huang-Wan, Qi-Ju-Di-Huang-Wan, Ji-Sheng-Shen-Qi-Wan and Ba-Wei-Di-Huang-Wan are derivative formulae of Liu-Wei-Di-Huang-Wan. In other words, Liu-Wei-Di-Huang-Wan and its derivatives were found to be the most common herbal formulae prescribed by TCM doctors for the treatment of diabetes in Taiwan. Conclusion. Although some evidence does support the use TCM to treat diabetes, the results from the current study may have been confounded by placebo effect, which emphasize the need for well conducted, double-blind, randomized, placebo-controlled studies in order to further evaluate the efficacy of Liu-Wei-Di-Huang-Wan on patients with type 2 diabetes.